The Quality of Alternative Coloring of Miana Leaves as a Substitute for Gentian Violet in Coloring Propionibacterium Acne Bacterial Preparations - Lenny Yustina Sarwom; Sri Martuti; Isnin Aulia Ulfah Mu’awanah (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2026)
Miana leaves (Coleus scutellarioides (L.) Benth) are known to contain anthocyanin pigments with a reddish-purple color that have potential as natural dyes. Anthocyanins are organic compounds soluble in polar solvents, capable of producing varied colors depending on pH, and commonly found in leaves and fruits. This study aimed to evaluate the quality of miana leaf extract as an alternative stain to replace gentian violet in the staining of Propionibacterium acne preparations. This experimental research applied different concentration ratios of miana leaf extract and distilled water, namely 1:1, 1:2, and 1:3. The results showed that the 1:3 concentration produced stronger color intensity and was closest to the positive control using gentian violet. Meanwhile, the 1:1 and 1:2 concentrations were less optimal due to weaker intensity, making bacterial morphology details less visible. Statistical analysis with the Kruskal-Wallis test confirmed significant differences among the groups. This study concludes that miana leaf extract, particularly at a 1:3 ratio, is effective as a natural alternative dye in Gram staining, offering a safer and more environmentally friendly substitute for synthetic stains such as gentian violet, which are known to have negative impacts on both health and the environment.